Biodegradation of Malathion Using Pseudomonas stutzeri(MTCC 2643) - S, Vaishali; A, Surendran; A.J, Thatheyus (Journal of Public Health International, 2020)
Pesticides are applied in agricultural fields for controlling pest population to achieve crop protection. But they cause damage to nontarget organisms and affect the quality of environment including water, air and soil. The present study has been designed to test the efficiency of Pseudomonas stutzerion the degradation of malathion. The bacterial strain was subjected to 50, 100, 150 and 200 ppm of malathion in minimal broth for 30 hours and changes in orthophosphate levels, pH and turbidity were monitored for every six hours. Efficiency of free and immobilized cells were compared for orthophosphate release. Influence of different sugars on degradation was also compared. Degradation of 150 ppm of malathion was confirmed with UV-Visible spectrophotometric analysis and HPLC analysis. The data were subjected to two way analysis of variance and the results are discussed.
Keywords: Biodegradation; Malathion; Pseudomonas stutzeri; Bacteria; Pesticide